Arthroscopy-assisted reduction for Jacob type II pediatric humeral lateral condyle fractures: a clinical efficacy study - Zhikai, Chen; Yuqing, Liu; Yifeng, Li; Jian, Wang; Tao, Jiang; Lin, Jiang; Fuping, Zhu (Frontiers in Pediatrics, 2025)
BackgroundMinimally invasive approaches are being increasingly employed in pediatric orthopedic trauma surgery. Clinical practice has seen applications of minimally invasive techniques for fractures such as intercondylar eminence avulsion fractures, femoral shaft fractures, and humeral shaft fractures. However, open reduction remains the primary surgical approach for pediatric humeral lateral condyle fractures. Open reduction disrupts peripheral blood circulation and increases the risk of epiphyseal injury. Damage to the epiphysis may affect a child's growth and development; therefore, surgical approach selection requires careful consideration. Our institution has accumulated substantial experience in applying arthroscopic techniques to trauma management. Through clinical exploration, we have developed an approach for treating pediatric humeral lateral condyle fractures involving arthroscopic reduction under endoscopic guidance combined with Kirschner wire fixation, aiming to provide new insights for clinical treatment.ObjectiveTo compare the efficacy of arthroscopic reduction vs. open reduction for Jacob type II pediatric humeral lateral condyle fractures.MethodsA retrospective study was conducted on 60 pediatric patients with Jacob type II humeral lateral condyle fractures treated at Liuyang Orthopedics Hospital between January 2021 and June 2022. The cases were divided into an Arthroscopic Group and an Open Reduction Group based on surgical approach. The Arthroscopic Group underwent arthroscopy-assisted reduction with Kirschner wire fixation, while the control group (Open Reduction Group) received open reduction with Kirschner wire fixation. Operative time, intraoperative blood loss volume, and incision length were compared between the two groups; Pre- and postoperative Visual Analog Scale (VAS) pain scores, C-reactive protein (CRP) levels, and erythrocyte sedimentation rate (ESR) were compared; To assess whether arthroscopic reduction offers advantages over open reduction for pediatric humeral lateral condyle fractures, outcomes including the Mayo Elbow Performance Score (MEPS) and Baumann angle were evaluated at 3 months postoperatively.ResultsIncisions healed by first intention in both groups. No statistically significant difference was found in operative time between groups [(30.17 ± 8.342) min vs. (29.07 ± 9.340) min, P = 0.632]. Incision length was significantly shorter in the Arthroscopic Group [(2.07 ± 0.254) cm vs. (4.63 ± 0.809) cm, P = 0.000]. Intraoperative bleeding was significantly less in the Arthroscopic Group [(7.59 ± 1.167) mL vs. (11.83 ± 2.706) mL, P = 0.012]. Both groups showed reduced VAS scores postoperatively, with significantly better scores in the Arthroscopic Group (P = 0.000). Postoperative CRP and ESR levels increased in both groups compared to preoperative values, but the Open Reduction Group demonstrated significantly greater increases (P < 0.05). At 3 months postoperatively, the Arthroscopic Group showed superior Mayo Elbow Performance Scores (P = 0.013), while no significant difference was observed in Baumann angle measurements.ConclusionArthroscopic reduction for pediatric humeral lateral condyle fractures offers smaller incisions, reduced bleeding, attenuated inflammatory response, and is more conducive to postoperative functional recovery.